Primary mucinous adenocarcinoma at the end ileostomy site with multiple metachronous colorectal cancers: A case report - Himanshu Shekhar; D Raghavendra; Loganathan Jayapal; K. R. Palaniswamy; Prasanna Kumar Reddy (World Journal of Colorectal Surgery)
Adenocarcinoma occurring at the end ileostomy site is a rare complication, with 70 cases reported in the literature to date. Most patients with adenocarcinoma occurring at the ileostomy site underwent total proctocolectomy for ulcerative colitis and familial adenomatous polyposis. Here, we present a case of adenocarcinoma arising at the end ileostomy site post total proctocolectomy for colorectal adenocarcinoma.